2019
DOI: 10.1088/1751-8121/ab1fcc
|View full text |Cite
|
Sign up to set email alerts
|

Péclet number governs transition to acceleratory restart in drift-diffusion

Abstract: First-passage processes can be divided in two classes: those that are accelerated by the introduction of restart and those that display an opposite response. In physical systems, a transition between the two classes may occur as governing parameters are varied to cross a universal tipping point. However, a fully tractable model system to teach us how this transition unfolds is still lacking. To bridge this gap, we quantify the effect of stochastic restart on the first-passage time of a drift-diffusion process … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 63 publications
3
109
0
1
Order By: Relevance
“…Appendix C: Proof of Eq. (38) In this Appendix, we will provide the proofs of the following relations…”
Section: (B11)mentioning
confidence: 99%
See 1 more Smart Citation
“…Appendix C: Proof of Eq. (38) In this Appendix, we will provide the proofs of the following relations…”
Section: (B11)mentioning
confidence: 99%
“…Second, restart has emerged as a conceptual framework to study search processes [29][30][31][32][33][34][35][36][37][38][39]. Consider a simple diffusive searcher looking for a target.…”
Section: Introductionmentioning
confidence: 99%
“…The simple model of diffusion with stochastic resetting has been extended and generalized to cover: diffusion in the presence of a potential [6][7][8], in a domain [9][10][11][12], and arbitrary dimensions [13]; diffusion in the presence of non-exponential resetting time distributions e.g., deterministic [14], intermittent [4], non-Markovian [15], non-stationary [16], with general time dependent resetting rates [17], as well as other protocols [18]; and diffusion in the presence of interactions [19][20][21]. The effect of resetting on random walks [22,23], continuous time random walks [24][25][26], Lévy flights [27,28], and other forms of stochastic motion [29][30][31][32][33], has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…No surprise that this observation has taken the center stage and lead to a myriad of studies. In particular, restart renders mean first passage time finite for many diffusive [1,2,[25][26][27]29,30] and nondiffusive search processes [18,21,28]. Further studies revealed existence of the dominant restart strategy which will globally optimize the MFPT [19,20,23], and a genre of universality relations associated with the optimally restarted processes [22,24].…”
mentioning
confidence: 99%
“…First-order transition in ORR was observed in the case of a nondiffusive search with the aid of Lévy flight [17] or a search comprising of a drifted random walker with exponential flights subjected to restart [21]. The continuous transition in the restart rate, on the other hand, was observed in a system of Brownian walker in a domain or force field subject to resetting [25][26][27]. Although each variant above carried with it some unique and alluring features, there exists no unified framework which can describe the existence of both the transitions in a single system and other higher-order features such as a shift in transition from being continuous to first order.…”
mentioning
confidence: 99%